Comparative Study of the Effectiveness of three Instructional Systems for Teaching Information Technology to Secondary School Students - Kumar, Rajender (INDIAN EDUCATIONAL REVIEW, 2007)
Information Technology is the fastest growing feld in India. Proper teaching of this subject at secondary level is very important. This study attempts to find out the best instructional method out of three i.e. Conventional Instructional System (CIS), Audio-Video Instructional System (AVIS) and Multimedia Instructional System (MIS) for teaching Information Technology at the secondary level. For this purpose total 120 students were randomly selected from three CBSE affiliated schools. They were assigned to three groups on the basis of their acores in Intelligence test. These three groups were taught by three different methods. Four tools were used in this study out of which, except for Intelligence test all other tools were developed by the researcher. After attaining the raw scores and applying different statistical techniques like ANOVA, t-test and factorial design, it was found that MIS is the best method, AVIS is the second best and CIS is the third best method for taking Information Technology at secondary level.